2020
DOI: 10.1136/openhrt-2020-001376
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of telephone triage in primary care patients with chest discomfort: a cross-sectional study

Abstract: ObjectiveTo assess the accuracy of semi-automatic assisted telephone triage in patients with acute chest discomfort against the diagnosis of acute coronary syndrome (ACS) or other life-threatening events (LTEs).MethodsA cross-sectional study was performed of telephone conversations with 2023 patients with acute chest discomfort (pain, pressure, tightness or discomfort) who called out-of-hours services for primary care (OHS-PC) between 2014 and 2016. Sensitivity, specificity, positive and negative predicted val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…23 A recent validation study showed that the diagnostic accuracy of the NTS for patients with chest discomfort was poor (sensitivity 0.73 (95% CI 0.68 to 0.78) and specificity 0.43 (95% CI 0.40 to 0.45)), as calculated on the outcome ACS or other life-threatening events (LTEs). 24 All telephone calls to the OHS-PC are routinely recorded and archived for 5 years for training and quality control purposes.…”
Section: Contextmentioning
confidence: 99%
“…23 A recent validation study showed that the diagnostic accuracy of the NTS for patients with chest discomfort was poor (sensitivity 0.73 (95% CI 0.68 to 0.78) and specificity 0.43 (95% CI 0.40 to 0.45)), as calculated on the outcome ACS or other life-threatening events (LTEs). 24 All telephone calls to the OHS-PC are routinely recorded and archived for 5 years for training and quality control purposes.…”
Section: Contextmentioning
confidence: 99%
“…The NTS is based on the Manchester triage system developed in and for the emergency department setting,7 8 and it may be over-ruled by the triage nurse, with or without consulting the supervising GP 2 7 9. However, the accuracy of the NTS has solely, and only recently, been validated against clinically relevant outcomes in the domains’ chest discomfort and neurological deficit 9–12. So, for other domains, it is still unknown if the urgency allocation is in line with clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, interviews with triage nurses revealed that the NTS may hinder triage, especially in very urgent calls where emotions of both triage nurses and patients are prominent during the telephone conversation 15. Previous studies from our research group showed that the accuracy of NTS was at the best moderate for patients with chest discomfort or suspected neurological deficits, and that both the NTS itself as working with the tool could be improved in these important domains 11 12 15 16. Thus, it is important to analyse the use of the NTS by triage nurses as well beside the NTS itself.…”
Section: Introductionmentioning
confidence: 99%
“… 12 13 The prevalence of ACS among patients with chest discomfort who call OHS-PC or EMS is about 10%–15%, and among those seen at the ED between 10% and 30%. 10 11 13 14 Only one prediction rule was developed in primary care for diagnosing ACS; the modified Grijseels prediction rule, which had moderate discriminative ability (c-statistic of 0.66) after external validation. 7 8 Five other primary care prediction rules were developed to predict CAD; for example, the Marburg Heart Score (MHS) and INTERCHEST prediction rule (International Working Group on Chest Pain in Primary Care).…”
Section: Introductionmentioning
confidence: 99%